2016
DOI: 10.1136/gutjnl-2015-310822
|View full text |Cite
|
Sign up to set email alerts
|

Stress-activatedmiR-21/miR-21*in hepatocytes promotes lipid and glucose metabolic disorders associated with high-fat diet consumption

Abstract: Michelangelo (2016). Stress-activatedmiR-21/miR-21*in hepatocytes promotes lipid and glucose metabolic disorders associated with high-fat diet consumption. Gut:gutjnl-2015-310822. DOI: https://doi.org/10.1136/gutjnl-2015 Stress-activated miR-21/miR-21* in hepatocytes promotes lipid and glucose metabolic disorders associated with high-fat diet consumption. How might it impact on clinical practice in the foreseeable future? Nicolas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 70 publications
(58 reference statements)
7
92
0
Order By: Relevance
“…3, 4 miR-21 is greatly increased in the liver of NASH patients 5 and in animal models of NASH. 6, 7, 8, 9 In hepatocytes, miR-21 is induced by unsaturated fatty acids in a mTOR/NF- κ B-dependent manner. 10 It was recently demonstrated that liver miR-21 has an active role in NASH pathogenesis through inhibition of nuclear receptor peroxisome proliferator-activated receptor α (PPAR α ).…”
mentioning
confidence: 99%
“…3, 4 miR-21 is greatly increased in the liver of NASH patients 5 and in animal models of NASH. 6, 7, 8, 9 In hepatocytes, miR-21 is induced by unsaturated fatty acids in a mTOR/NF- κ B-dependent manner. 10 It was recently demonstrated that liver miR-21 has an active role in NASH pathogenesis through inhibition of nuclear receptor peroxisome proliferator-activated receptor α (PPAR α ).…”
mentioning
confidence: 99%
“…Unexpectedly, levels of nucleotides as well as methionine and its derivative S-adenosylmethionine were not decreased upon knockdown of MTHFD1L (Supplemental Figure 5, A and B). NADPH is required for lipid synthesis, which supports HCC development (30)(31)(32). We performed Oil Red O staining to quantitate the levels of triglycerides and lipids in the MTHFD1L-knockdown HCC cells and in HCC tumors treated with antifolate drug (methotrexate, MTX); however, no significant difference in lipid metabolism could be detected (Supplemental Figure 5, C and D).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of murine miRNA-21 specifically in hepatocytes indicated a crucial role for hepatic miRNA-21 in metabolic disorders associated with diet-induced obesity. Deletion of miRNA-21 in hepatocytes increased insulin sensitivity and modulated the expression of multiple key metabolic transcription factors involved in fatty acid uptake, de novo-lipogenesis, gluconeogenesis and glucose output [311]. Furthermore, long-term inhibition of miRNA-21 reduced body weight and adipocyte size in db/db mice [312].…”
Section: Milk-mediated Epigenetic Signaling and Diseases Of Civilmentioning
confidence: 99%